Bedside clinical neurologic assessment utilisation in paediatric cardiac intensive care units. (16th October 2018) - Kirschen, Matthew P; Blinder, Josh; Dewitt, Aaron; Snyder, Megan; Ichord, Rebecca; Berg, Robert A; Nadkarni, Vinay; Topjian, Alexis
Abstract: Introduction: Neurodevelopmental disabilities in children with CHD can result from neurologic injury sustained in the cardiac ICU when children are at high risk of acute neurologic injury. Physicians typically order and specify frequency for serial bedside nursing clinical neurologic assessments to evaluate patients' neurologic status. Materials and methods: We surveyed cardiac ICU physicians to understand how these assessments are performed, and the attitudes of physicians on the utility of these assessments. The survey contained questions regarding assessment elements, assessment frequency, communication of neurologic status changes, and optimisation of assessments. Results: Surveys were received from 50 institutions, with a response rate of 86%. Routine clinical neurologic assessments were reported to be performed in 94% of institutions and standardised in 56%. Pupillary reflex was the most commonly reported assessment. In all, 77% of institutions used a coma scale, with Glasgow Coma Scale being most common. For patients with acute brain injury, 82% of institutions reported performing assessments hourly, whereas assessment frequency was more variable for low-risk and high-risk patients without overt brain injury. In all, 84% of respondents thought their current practice for assessing and monitoring neurologic status was suboptimal. Only 41% felt that the Glasgow Coma Scale was a valuable tool for assessing neurologic function in the cardiac ICU, and 91% felt that a standardised approach to assessing pre-illness neurologic function would be valuable. Conclusions: Routine nursing neurologic assessments are conducted in most surveyed paediatric cardiac ICUs, although assessment characteristics vary greatly between institutions. Most clinicians rated current neurologic assessment practices as suboptimal.